Computer vision for skin colour invariant detection of face acne & pigmentation - Chaudhary, Nidhi Narsingh (Nanyang Technological University, 2023)
It is important to take good care of facial skin. However, for an average consumer, it can be challenging to understand what issues our skin can face. Additionally, getting the opinion of a dermatologist for just mild skin issues can be unnecessarily expensive. With acne and pigmentation being some of the most common dermatological issues, the healthcare industry is looking for ways to automate the diagnosis and detection of such spots. However, there is a lack of research into creating a model that performs well in detecting facial spots across all skin tones.